Experimental analysis of moisture content with involuntary irrigation structure in soil. (2021) - Anton Amala Praveen, A.; Tamilnesan, P.; Muthukumaran, M.; Udayakumar, M.D.
Abstract: Agriculture is the backbone of this world. It is an important segment growing worldwide due to population growth. The main problem in the agricultural segment is the development of farm yields with good agricultural supremacy. It could be achieved with continuous automated monitoring to gather the fast-growing food requirement. Climate changes are the biggest issue in the agricultural sector due to the increase in the world population. In this research work, a sophisticated farming technique has been adapted based on Internet of Things (IoT) to deal with the unfavorable conditions. This proposed farming method can be provided with highest possible accuracy of crop control and collection of various functional statistics with computerized control. Temperature and soil humidity are monitored with suitable observation system by an intellectual agriculture pasture. Without human participation, the sensing data shall be analyzed and the necessary steps can be taken with the above data. In this research work, Measurement parameters temperature and soil moisture are taken as measurement parameters. With the sufficient statistical analysis, they could be processed with the help of ThingSpeak cloud application.